High prevalence of self-reported sexually transmitted infections among older adults in Tanzania: results from a list experiment in a population-representative survey - Kim, Hae-Young; Rohr, Julia; Leyna, Germana Henry; Killewo, Japhet; Tomita, Andrew; Tanser, Frank; Bärnighausen, Till (Annals of epidemiology, 2023)
Purpose - Self-report of sensitive or stigmatized health states is often subject to social desirability and interviewer biases. To reduce such biases, we estimated the rate of sexually transmitted infections (STIs) using a list experiment. - Methods - This population-representative study was nested within the Dar es Salaam Urban Cohort Study, a Health and Demographic Surveillance System (HDSS) in the Ukonga ward of Dar es Salaam, Tanzania. Men and women aged ≥40years were randomly assigned to receive a list of either four control items (i.e., the control group) or four control items plus an additional item on having had a disease through sexual contacts in the past 12months (i.e., the treatment group). We calculated the mean difference in the total number of items to which respondents answered “yes” in the treatment versus control group and compared this prevalence estimate to the one measured by the direct question. - Results - A total of 2310 adults aged ≥40years were enrolled in the study: 32% were male and 48% were aged 40-49years. The estimated prevalence of having STIs in the past 12months was 17.8% (95% confidence interval [CI] 12.3-23.3) in the list experiment, almost 10 times higher than the estimated prevalence of 1.8% (95%CI 1.3-2.4) based on the direct question (P < .001). STI prevalence remained high after adjusting for age, the number of lifetime sex partners, alcohol consumption and smoking in multivariate linear regression (15.6%; 95% CI 7.3-23.9). - Conclusions - We found a substantially higher prevalence of STIs among older adults in urban Tanzania when we based our estimation on a list experiment rather than a direct question in a population-representative survey. List experiments should be considered to elimnate social desirability and interviewer biases in surveys of sensitive or stigmatized health states. The very high prevalence of STIs highlights the need for improved access to STI screening, prevention and treatment for older adults in urban Africa.
Online verfügbar: 16. Mai 2023, Artikelversion: 14. Juli 2023
Gesehen am 06.10.2023